2015
DOI: 10.1309/ajcpixuydvz0rz3g
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tumor-Infiltrating Lymphocytes and the Tertiary Lymphoid Structures in HER2-Positive Breast Cancer Treated With Adjuvant Trastuzumab

Abstract: Abundant TILs are an independent prognostic factor in HR-/HER2+ breast cancers. Evaluation of TILs in HR-/HER2+ breast cancers may provide valuable information regarding the prognosis of patients treated using adjuvant chemotherapy and trastuzumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 37 publications
(51 reference statements)
9
91
1
Order By: Relevance
“…Several reports have indirectly supported the hypothesis that peripheral blood T and B lymphocytes are marshaled to TLSs and that differentiated cells migrate to the tumor, where they develop into TILs [3,25,26]. In this study, we showed that a high level of TILs was significantly associated with the abundance of TLSs around both the invasive component and DCIS, which also indirectly supported the above hypothesis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Several reports have indirectly supported the hypothesis that peripheral blood T and B lymphocytes are marshaled to TLSs and that differentiated cells migrate to the tumor, where they develop into TILs [3,25,26]. In this study, we showed that a high level of TILs was significantly associated with the abundance of TLSs around both the invasive component and DCIS, which also indirectly supported the above hypothesis.…”
Section: Discussionsupporting
confidence: 87%
“…Lymphoid accumulation containing vessels with high endothelial venule features (plump and cuboidal endothelial cells) was considered to be the TLS (Fig. 1C) [3]. We evaluated the ducts involved by DCIS with surrounding TLSs as a percentage of total ducts involved by DCIS and the amount of TLSs as a percentage of the total circumference of the invasive edge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLSs are ectopic, vascularized lymphoid formations that can be found in inflamed or tumoral tissues [7]. In breast cancers, TLSs can be observed mainly in areas that surround the tumor and adjacent normal terminal ductal lobular units [8]. The mechanism whereby TLSs are formed is not known, but the roles for high endothelial venules (HEVs) and the chemokine CXCL13 have been suggested [9].…”
Section: Introductionmentioning
confidence: 99%
“…1,[15][16][17][18] Conversely, tumors can also recruit immune cells with potential antitumor activities, such as NK cells or T cells, 17 which have been shown to suppress cancer progression and improve outcome in melanoma, 19,20 colorectal 21 and breast cancers. 22,23 Mobilized CD11b C cells may be arrested in their differentiation by tumor-derived factors and accumulate in blood, spleen and in the tumor microenvironment as myeloid-derived cells with immunosuppressive features (myeloid-derived suppressor cells (MDSC): CD11b…”
Section: Introductionmentioning
confidence: 99%